Mumps interstitial nephritis: A case report - Kabakuş, Nimet; Aydino?lu, Hakan; Bakkalo?lu, Sevcan A.; Yekeler, Hayrettin (My University, 1999)
Mumps is still a common childhood disease in rural areas where mumps vaccination is not widespread. A 14-year-old girl with fatal interstitial nephritis as a complication of mumps is reported. The patient had not been vaccinated with mumps vaccine and had contracted mumps during a village epidemic. The illness began with parotitis, and renal insufficiency developed within a week. The patient's renal function rapidly deteriorated and the outcome was fatal. The postmortem renal necropsy sample demonstrated interstitial mononuclear cell infiltration, edema, and focal tubular epithelial cell damage, confirming the clinical diagnosis. In developing countries routine mumps vaccination may help to prevent possible fatal complications of mumps. Furthermore, patients with mumps, especially complicated cases, should be followed closely.
Keywords: Fatal nephritis; Interstitial nephritis; Mumps